Hvad karakteriser vækkelsesbevægelser, der kalder sig lutherske? - Kofod-Svendsen, Flemming (Kirkehistoriske Samlinger, 2017)
Luther ønskede både som professor og prædikant først og fremmest at være bibeludlægger og bibelformidler. Som et bidrag til at markere reformationens 500-årsjubilæum vil denne artikel beskrive, hvordan nogle grupper, der er vokset ud af det 19. århundredes religiøse vækkelser, og som i hele deres historie på forskellig måde har profileret sig som lutherske, i praksis har læst, forstået og brugt Luther. Summary What characterizes awakening movements that define themselves as Lutheran? This study shows that movements that were results of the religious awakening movements of the 19th Century and which by their names and in public declarations defined themselves as Lutheran do not necessarily understand and use Luther in the same way. Concerning article 4 in the Augsburg Confession about justification by faith – traditionally considered the main article of the Lutheran reformation – the four movements in question are mainly in concordance. Both the proclamation of law and gospel, and their views of sin and grace are mattes of agreement. DELF is the organization that has made the broadest use of Luther in its preaching and has made use of a multitude of Luther texts – the postils, the great Commentary on the Letter to the Galatians, the small and the large catechisms, devotional books by Luther, the reformation writings and the Tract on the Bondage of the Will. KLT has mainly been using Luther’s postils and Luther’s two catechisms together with devotional books by Luther. ELM has generally been focusing on Luther’s Greater Commentary on Galatians, which has been quoted repeatedly. LM always took its point of departure in the writings of C.O. Rosenius. He was the editor of the periodical Pietisten in which he often quoted Luther. Sometimes quotations of Luther’s Postils or the Commentary on the Galatians were the only contents of the issued copies. During the first 125 years of LM’s history Luther did not play the same central role as he did in other organizations. The LM seems to have reached its understanding of justification by faith through the study of Rosenius. The LM in its early history primarily used Luther as legitimation of its low-church profile – pointing to Luther’s concept of the priesthood of all believers. A more general use of Luther did not evolve until the younger generation of the organization began studying theology – and the Credo Publishing House published its translations of Luther’s works 1981-1996. The very different use of Luther in the four organizations become so much more clear in their ecclesiology comprising their attitudes to ministry and the significance and weight of the sacraments. The DELF has been stressing the importance of the ordained pastor as the spiritual guide, preacher, ministrant, and counselor of the local congregation. Also in the KLT it has been stressed that the congregation be led by a chosen and consecrated person – but it has not in the strict manner as the DELF denounced lay-preachers. LM on the other hand has been emphasizing that the called lay-preacher possess the spiritual right to execute the same functions as an ordained pastor of the official church. ELM has a wider understanding of the ministry of the church than the LM. However, the ELM has been underlining the need of a sound biblical-Lutheran doctrine unto a degree that the organization was only prepared to work together with a very few pastors of the official church. The establishment of Menighedsfakultetet (The Lutheran School of Theology in Aarhus) and the Dansk Bibel-Institut (Danish Bible-Institute) changed this attitude. ELM has a more positive understanding of ministry than the LM – but the sacraments were traditionally given a higher significance by DELF and KLT than by LM and ELM. As the official Danish Church launched a ritual for marriage of homosexual persons, it meant that many members of the LM left the official church and established free congregations. Some members have left the ELM in protest against the new ritual and sought shelter in free congregations. Historically the disagreement in the understandings of church and ministry has meant that the four Lutheran organizations have not been able to cooperate in their original and mutual agreement on the justification by faith.